Islamic Democracy and Moderate Muslims - M. A. Muqtedar Khan (International Institute of Islamic Thought, 2005)
Question 1: Various commentators have frequently invoked the importance of moderate Muslims and the role that they can play in fighting extremism in the Muslim world. But it is not clear who is a moderate Muslim. The recent cancellation of Tariq Ramadan’s visa to the United States, the raids on several American Muslim organizations, and the near marginalization of mainstream American Muslims in North America pose the following question: If moderate Muslims are critical to an American victory in the war on terror, then why does the American government frequently take steps that undermine moderate Muslims? Perhaps there is a lack of clarity about who the moderate Muslims are. In your view, who are these moderate Muslims and what are their beliefs and politics?